2008
DOI: 10.1007/s00383-008-2294-6
|View full text |Cite
|
Sign up to set email alerts
|

Results of a practical protocol for management of prenatally detected hydronephrosis due to ureteropelvic junction obstruction

Abstract: Pyeloplasty may be performed safely in infants when indicated; however, the majority of children with UPJO can be managed conservatively. Spontaneous resolution of hydronephrosis and/or favorable prognosis was encountered in 87% of conservatively managed RU. The use of a standard US grading system, selective utilization of follow-up renal function testing, and parental compliance are important factors in successful management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 19 publications
0
22
0
1
Order By: Relevance
“…We observed that the ratio of C/P was significantly improved postoperatively in both groups but greater in the early pyeloplasty group. Different follow-up protocols have been suggested by different authors [7,26]. Some authors have used US as a main diagnostic tool during follow-up.…”
Section: Discussionmentioning
confidence: 98%
“…We observed that the ratio of C/P was significantly improved postoperatively in both groups but greater in the early pyeloplasty group. Different follow-up protocols have been suggested by different authors [7,26]. Some authors have used US as a main diagnostic tool during follow-up.…”
Section: Discussionmentioning
confidence: 98%
“…5) [38]. Its incidence in children with ANH varies greatly between studies from 5% to 64% of patients [49,51,52]. The variability corresponds to differences in the management of these children, from early surgery to close observation until renal function deterioration or progression of hydronephrosis occurs.…”
Section: Upj Obstructionmentioning
confidence: 91%
“…Postnatal assessment should start on day 3 or 4 of life since US earlier than this can lead to false negative results [2,3]. If no dilatation is detected, a repeat US should be performed within 4-6 weeks to avoid the possibility of a genuine obstructive uropathy that can be masked by transient oliguria.…”
Section: Introductionmentioning
confidence: 99%